Herpes Simplex Virus Vectors for Gene Transfer to the Central Nervous System - Sara Artusi; Yoshitaka Miyagawa; William F. Goins; Justus B. Cohen; Joseph C. Glorioso (Diseases, 2018)
Neurodegenerative diseases (NDs) have a profound impact on human health worldwide and their incidence is predicted to increase as the population ages. ND severely limits the quality of life and leads to early death. Aside from treatments that may reduce symptoms, NDs are almost completely without means of therapeutic intervention. The genetic and biochemical basis of many NDs is beginning to emerge although most have complex etiologies for which common themes remain poorly resolved. Largely relying on progress in vector design, gene therapy is gaining increasing support as a strategy for genetic treatment of diseases. Here we describe recent developments in the engineering of highly defective herpes simplex virus (HSV) vectors suitable for transfer and long-term expression of large and/or multiple therapeutic genes in brain neurons in the complete absence of viral gene expression. These advanced vector platforms are safe, non-inflammatory, and persist in the nerve cell nucleus for life. In the near term, it is likely that HSV can be used to treat certain NDs that have a well-defined genetic cause. As further information on disease etiology becomes available, these vectors may take on an expanded role in ND therapies, including gene editing and repair.